2017
DOI: 10.1074/jbc.m117.779520
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 Protein Expression Is Increased in Human Diabetic Nephropathy

Abstract: There is very limited human renal sodium gradient-dependent glucose transporter protein (SGLT2) mRNA and protein expression data reported in the literature. The first aim of this study was to determine SGLT2 mRNA and protein levels in human and animal models of diabetic nephropathy. We have found that the expression of SGLT2 mRNA and protein is increased in renal biopsies from human subjects with diabetic nephropathy. This is in contrast to db-db mice that had no changes in renal SGLT2 protein expression. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(118 citation statements)
references
References 74 publications
6
110
0
2
Order By: Relevance
“…The present study supports the results of previous studies that demonstrated that DAPA improved the glucose control and levels of C-peptide. [38,39] Moreover, treatment with LPZ significantly decreased the blood glucose and C-peptide levels as compared with the levels in the DC group; these results were in line with those of the previous study [18] that revealed that the glucose-lowering effect of LPZ was a result of increased secretion of gastrin by PPIs. [40] As previously reported, gastrin stimulated β-cell neogenesis and mass expansion.…”
Section: Discussionsupporting
confidence: 88%
“…The present study supports the results of previous studies that demonstrated that DAPA improved the glucose control and levels of C-peptide. [38,39] Moreover, treatment with LPZ significantly decreased the blood glucose and C-peptide levels as compared with the levels in the DC group; these results were in line with those of the previous study [18] that revealed that the glucose-lowering effect of LPZ was a result of increased secretion of gastrin by PPIs. [40] As previously reported, gastrin stimulated β-cell neogenesis and mass expansion.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, Hosokawa et al showed that Ipragliflozin decreases ectopic lipid accumulation in tubular cells in diabetic mice [238]. In db/db mice, JNJ 39933673, a selective SGLT2i, prevented renal lipid accumulation by inhibition of transcription factor carbohydrate-responsive element-binding protein (ChREBP) β-isoform, a transcription factor that mediates activation of several regulatory enzymes of glycolysis and lipogenesis pathway such as SCD-1 and diacylglycerol O-acyltransferase-1 (DGAT1) [191]. Although further studies are needed overall, it is plausible that, in addition to the well-known effects of SGLT2i (anti-inflammatory, anti-proliferative, and anti-fibrotic), the reduction of tubular lipid deposition could be a new renoprotective mechanism of these molecules [192,239,240].…”
Section: Sglt-2 Inhibitorsmentioning
confidence: 99%
“…The effect is enhanced in the setting of hyperglycemia since the latter increases the filtered load of glucose to the proximal tubule, which enhances glucose reabsorption via SGLT2 and as a consequence the glucosuric effect of SGLT2 inhibition. This glucosuric effect may further increase due to a diabetes-associated increase in renal SGLT2 expression, although this remains a matter of debate due to positive and negative data [25]. Thus, diabetes increases renal glucose reabsorption via SGLT2, which contributes to maintain hyperglycemia, and SGLT2 inhibition opposes these effects.…”
Section: Sglt2 Inhibitors Are Anti-hyperglycemic Drugs With Low Hypogmentioning
confidence: 99%